Epidemiological studies of bovine digital dermatitis in pasture-based dairy system in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Sciences at Massey University, Palmerston North, New Zealand - Yang, Danchen (Massey University, 2019)
Bovine digital dermatitis (BDD) is an infectious disease of the feet of cattle. Worldwide, it is one of the most commonly observed foot diseases on many dairy farms, and is the most important infectious cause of lameness in cattle in confined dairy system. Although BDD is generally less common in pasture-based dairy system it can still cause significant production losses and welfare issues, in such systems. This thesis contains seven original research works covering the epidemiological aspects of BDD in pasture-based cattle in New Zealand. Firstly, cross-sectional and longitudinal data obtained from Taranaki were analysed to identify the factors (including climate) associated with the disease. This was followed by a large scale cross-sectional study covering four regions in New Zealand looking at the prevalence of and risk factors for BDD. A longitudinal study was then undertaken on three farms in order to collect disease data (including BDD lesion type) over a lactation. Using this dataset, a deterministic compartment model was built to study the transmission dynamics of BDD within a dairy herd in New Zealand. Along with these large studies, two small validation studies were also carried out. The first study evaluated the agreement between two trained BDD observers in determining BDD presence/ absence in digital photographs, while the second one evaluated the reliability of clinical examination of BDD lesions in the milking parlour without prior washing of the animals’ feet. This work suggests that BDD has spread widely across New Zealand, although it has yet to reach the West Coast. In the four regions where BDD was identified, true between herd prevalences varied by region (from ~ 40% to > 65%). Furthermore, although BDD was found in many herds, true cow level prevalence was low in all affected regions, being generally less than 4% in affected herds. Several biosecurity related management practices were repeatedly identified as factors associated with increased BDD prevalence at both the herd and cow level. These included mixing heifers with animals from other properties; purchasing heifers for replacement and using outside staff to treat lame cows. In addition to the identified management practices, climate (rainfall and soil temperature) was also found to have had a significant association with the prevalence of BDD. These studies used examination in the milking parlour as the method of identifying BDD lesions. This method while the best method of lesion detection for large scale studies is not perfect. It generally requires that feet are washed prior to examination, as lesions masked by dirt are difficult to identify. Our study quantified the effect, under New Zealand conditions, of feet washing prior to examination finding sensitivities of 0.34 (95% credible interval [CrI]: 0.088-0.69) and 0.63 (95%CrI: 0.46- 0.78) for pre- and post-washing, respectively. There was a 93.95% probability that the sensitivity of examination post-washing was greater than that prewashing. Limited information on the reliability of examination in the milking parlour prompted comparison of two trained observers using digital photographs. Agreement between the two observers was good; we could be 75% sure that the two observers had almost perfect agreement and 95% sure the two observers had at least substantial agreement. It is crucial that since examination in the milking parlour is not a perfect reference test for detecting BDD lesions that when estimating prevalence, the sensitivity and specificity of this method is factored into the analysis. This is often achieved using an approach based on the binomial distribution. However, as the dairy herd is a finite population and the sampling of animals for BDD lesion is effectively sampling without replacement, the correct distribution to use is the hypergeometric one. This is computationally complex so the Bayesian superpopulation approach was developed to allow continued use of the binomial distribution. The superpopulation approach was used to estimate prevalence in this thesis, one of the first uses of this approach in the veterinary field. The appearance of BDD in New Zealand is different from that elsewhere. Most lesion have been observed are small grey, rubbery lesions which may or may not have thickened, darker edges. Less commonly larger, more proliferative lesions can also be found. Red active lesions are extremely rare. Post-treatment lesions are not a feature of the disease in New Zealand as lesions are treated only very rarely. Thus modelling approach used a BDD score system which focuses on early stage of BDD. This found that in infected dairy herds, although BDD prevalence will tend to increase year-on-year it is likely to remain relatively low (<18%) even after 10 years of within-herd transmission. It is likely that the low transmission rate during the late lactation (model assumption) results in more cases resolving than developing during this period and therefore results in the low prevalence of infectious cattle at the start of each subsequent lactation. Cattle with larger, more proliferative lesions had a stronger influence on the establishment and maintenance of DD than cattle with small lesions highlighting the importance of targeting these animals for intervention.
Listed in 2020 Dean's List of Exceptional Theses
Appendices 1, 2, 3, 6 & 7 were removed for copyright reasons, but the published articles may be accessed via the following links: Appendix 1. Farm level risk factors for bovine digital dermatitis in Taranaki, New Zealand: An analysis using a Bayesian hurdle model https://doi.org/10.1016/j.tvjl.2018.02.012 Appendix 2. Effects of climate and farm management practices on bovine digital dermatitis in spring-calving pasture-based dairy farms in Taranaki, New Zealand https://doi.org/10.1016/j.tvjl.2019.03.004 Appendix 3. Estimating the herd and cow level prevalence of bovine digital dermatitis on New Zealand dairy farms: A Bayesian superpopulation approach https://doi.org/10.1016/j.prevetmed.2019.02.014 Appendix 6. Inter-observer agreement between two observers for bovine digital dermatitis identification in New Zealand using digital photographs https://doi.org/10.1080/00480169.2019.1582369 Appendix 7. Detecting bovine digital dermatitis in the milking parlour: To wash or not to wash, a Bayesian superpopulation approach https://doi.org/10.1016/j.tvjl.2019.02.011
Keywords: Dairy cattle; Diseases; Epidemiology; New Zealand; Hoofs; Skin; Inflammation; Dean's List of Exceptional Theses; 300905 Veterinary epidemiology